NUEVOS PLANES, IDÉNTICAS ESTRATEGIAS: APUNTES SOBRE UN CINE ASTURIANO ACTUAL - Pablo Sánchez Blasco, (Fonseca, Journal of Communication, 2023)
This article pays attention to the condition of the Asturian audiovisual production, especially during the last three years. After the disappearence of the grants and investments in culture, a group of young filmmakers has emerged with low-cost independent films that have standardized the full-lenght film as their main target. Their characteristics approach them to the “Other Spanish Cinema” although, at the same time, they show particular circumstances that distinguish their productions.